Analysis of Monetary Strategies and Policies to Manage the Inflation and Public Purchasing Power in Indonesia - Wartoyo, Wartoyo; Lutfiyanti, Lutfiyanti; Ainun, Ayi Siti (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
This study aims to analyze how the strategies and monetary policies implemented by Bank Indonesia in managing inflation and increasing people's purchasing power in Indonesia. Inflation and purchasing power are interrelated, by keeping inflation stable, prices for goods and services maintained, and people's purchasing power increasing so as to encourage Indonesia's sustainable economic growth. The research in this article uses library research, while the data used is secondary data obtained from several sources, including the Central Statistics Agency (BPS), Bank Indonesia and the Institute for Development of Economics and Finance (INDEF). Based on the results of this study, it was found that Indonesia will experience 5.51% inflation throughout 2022. Throughout 2022, the highest inflation was recorded in the transportation expenditure group, namely 15.26% with a share of 1.84%. Meanwhile, the contribution of household consumption decreased to 51.7% compared to 2021 of 52.9%. The government is currently continuing to coordinate with Bank Indonesia through monetary policies to control this inflation.